Colombia Government Debt and Risk Management Program : Outcomes and Implemented Reforms - Cabral, Rodrigo; Scipioni, Alessandro (World Bank, Washington, DC, 2016)
Effective public debt management is a cornerstone of financial stability and sustainable fiscal policy. The composition of public debt has been an important factor in many economic and financial crises, as excessive exposure to changes in exchange rates and interest rates can result in large negative impacts on public finances. During the 2008-2009 crisis, however, middle-income countries generally performed well. The Colombian government has embarked on a series of reforms aimed at reducing vulnerability of the government’s balance sheet to financial shocks. This report summarizes the main outcomes of the Government Debt and Risk Management Program (GDRM) in Colombia. The World Bank (WB) delivered this technical assistance (TA) through its Government Debt and Risk Management (GDRM) program, supporting Colombia, in particular the General Directorate of Public Credit and National Treasury (DGCPTN), in implementing the priority public debt management reforms. This report summarizes the main outcomes achieved by the DGCPTN under the GDRM framework, which has a strong focus on outcomes. The report is divided into five sections, with each section corresponding to a focus area of the GDRM program. In turn, each section is divided in three subsections as follows: (i) progress made until March 2016; (ii) recommendations for further strengthening public debt and cash management in the respective areas; and (iii) potential future technical assistance as discussed with the authorities during the latest mission (March 2016).